1990
DOI: 10.1111/j.1432-1033.1990.tb19161.x
|View full text |Cite
|
Sign up to set email alerts
|

Interdependence of tumor necrosis factor, prostaglandin E2, and protein synthesis in lipopolysaccharide‐exposed rat Kupffer cells

Abstract: Kupffer cells are the main producers of tumor necrosis factor‐α (TNF; cachectin) and eicosanoids in the liver exposed to lipopolysaccharide (endotoxin; LPS). A very rapid but transient release of TNF is followed by a slow, steady synthesis of prostaglandin E2 (PGE2). TNF itself is able to provoke eicosanoid synthesis in Kupffer cells; the rate and pattern of prostaglandin production are similar to those observed after treatment with LPS. Anti‐TNF antibodies completely neutralize TNF action on Kupffer cells, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(30 citation statements)
references
References 37 publications
0
29
1
Order By: Relevance
“…Upon stimulation with endotoxin these cells produce a variety of cytokines, lipid mediators and radicals. Recent studies have indicated that endotoxin enhances the expression of inducible cyclooxygenase-2 (Cox-2) [2][3][4][5][6], which results in the increased formation of prostanoids by Kupffer cells and other macrophages [3,[7][8][9]. Interestingly, lipopolysaccharide (LPS)-induced prostaglandin E2, D2 and thromboxane B2 formation and Cox-2 expression are stimulated up to 10-fold when ambient osmolarity increases from 300 to 350 mosmol/1 [3].…”
Section: Introductionmentioning
confidence: 99%
“…Upon stimulation with endotoxin these cells produce a variety of cytokines, lipid mediators and radicals. Recent studies have indicated that endotoxin enhances the expression of inducible cyclooxygenase-2 (Cox-2) [2][3][4][5][6], which results in the increased formation of prostanoids by Kupffer cells and other macrophages [3,[7][8][9]. Interestingly, lipopolysaccharide (LPS)-induced prostaglandin E2, D2 and thromboxane B2 formation and Cox-2 expression are stimulated up to 10-fold when ambient osmolarity increases from 300 to 350 mosmol/1 [3].…”
Section: Introductionmentioning
confidence: 99%
“…Upon stimulation with endotoxin these cells produce a variety of cytokines, lipid mediators and radicals. Recent studies have indicated that endotoxin enhances the expression of inducible cyclooxygenase-2 (Cox-2) [2~5], which results in an increased formation of prostanoids by Kupffer cells and other macrophages [3,[7][8][9]. This response to LPS is markedly enhanced in hyperosmotic environments due to an about 10-fold stimulation of *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…20 The anti-inflammatory action of PGE 2 on Kupffer cells is mediated via G s -coupled PGE 2 receptors and an increase in intracellular cyclic adenosine monophosphate (cAMP). 17 Kupffer cells have been shown to express both G s -coupled PGE 2 receptors, the EP2-R and the EP4-R. 20 In addition to its anti-inflammatory action on Kupffer cells, PGE 2 has been shown to decrease the cytokine-stimulated de novo synthesis of acute phase proteins in rat hepatocytes. 21 It would seem logical, that such an anti-inflammatory action of PGE 2 on hepatocytes should also be mediated by G s -coupled PGE 2 receptors.…”
mentioning
confidence: 99%